2021
DOI: 10.1155/2021/5555406
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Carbon from Optimized Date Stone Hydrochar by Catalytic Hydrothermal Carbonization Using Response Surface Methodology: Application to Dyes Adsorption

Abstract: Providing efficient and environmental friendly ways to recover lignocellulosic waste remains a challenge around the world. In this study, citric acid-catalyzed hydrothermal carbonization (CHTC) was coupled with pyrolysis to convert date seed (Ds) into adsorbent material. In this regard, a central composite design (CCD) using response surface methodology (RSM) was developed to examine the influence of temperature, reaction time, and catalyst dose on the mass yield (Ym(%)) and carbon retention rate (CRR(%)) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 70 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…Several studies revealed that some adsorbate-adsorbents systems produced high R 2 values for both Langmuir and Freundlich models, which signified that those adsorption systems can be well-described by two isotherm models (Daoud et al, 2017;El Ouadrhiri et al, 2021). This phenomenon can be explained by the existence of both homogenous and heterogeneous types of surfaces on the adsorbent.…”
Section: Adsorption Isothermsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies revealed that some adsorbate-adsorbents systems produced high R 2 values for both Langmuir and Freundlich models, which signified that those adsorption systems can be well-described by two isotherm models (Daoud et al, 2017;El Ouadrhiri et al, 2021). This phenomenon can be explained by the existence of both homogenous and heterogeneous types of surfaces on the adsorbent.…”
Section: Adsorption Isothermsmentioning
confidence: 96%
“…In the literature, only few publications have employed the HTC method to convert DPR into hydrochar. In a study performed by El Ouadrhiri et al (2021), optimum preparation conditions for date seed-based hydrochar (OHC-DS) were found to be 200 °C, 120 min, and 20 mg of temperature, reaction time, and catalyst dose (citric acid), respectively, which corresponded to hydrochar yield of 59.71% and 75.84% of the carbon retention rate. It was observed that when the temperature and residence time were increased from 160 to 240 °C and from 32 to 120 min, respectively, the yield of OHC-DS decreased accordingly.…”
Section: Hydrothermal Carbonization (Htc) Processmentioning
confidence: 99%
“…Demir-Cakan et al and Heidari et al have similar reports. Susanti et al synthesized activated carbon with a higher SSA by adding a little amount of CA during HTC, and El Ouadrhiri et al have a similar report. , However, there are limited reports that used this method to achieve a high SSA and high specific capacitance, and most of their SSA are below 2000 m 2 /g. To the best of our knowledge, the research on the effect of catalytic HTC on the properties of porous carbon is still very limited . Therefore, to further study the effect of adding additives during HTC on the pore structure and electrochemical properties of porous carbon is very necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Susanti et al synthesized activated carbon with a higher SSA by adding a little amount of CA during HTC, and El Ouadrhiri et al have a similar report. 46,47 However, there are limited reports that used this method to achieve a high SSA and high specific capacitance, and most of their SSA are below 2000 m 2 /g. 48−50 To the best of our knowledge, the research on the effect of catalytic HTC on the properties of porous carbon is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a long-standing interest in making OP a source of valuable materials (Aliakbarian, Casazza, and Perego 2011). The HTC has attracted lot of attention compared to other waste pretreatment techniques, because it generates a product rich in carbon (El Ouadrhiri et al 2021), and contributes to the reduction of gaseous emissions and the elimination of the energy-intensive wet feedstock drying process (Titirici 2015). Inspired by these facts, the aim of the present study is rst to synthesize a porous material functionalized by two heteroatoms, nitrogen, and phosphorus, from olive pomace as a renewable carbon source, using the HTC process catalyzed by a doping precursor, and then to test the e ciency of the doped and co-doped synthesized materials in the degradation of organic pollutants in the presence of persulfate.…”
Section: Introductionmentioning
confidence: 99%